Expanded media in the Malaysian contemporary Arts practice - Wan Abdullah Thani, W.J.I (Universiti Malaysia Sarawak, 2007)
Article in Hybrid+ism 2007 (Publication in conjunction with Hybrid+ism 2007 Exhibition, Sabah Art Gallery Kota Kinabalu)